Tyranny, Inc. : how private power crushed American liberty-- and what to do about it - Ahmari, Sohrab (Forum Books, an imprint of Penguin Random House LLC, 2023)
"The inside story of how our political class enabled an era of unaccountable corporate might that left ordinary Americans isolated and powerless--and how we can fight back-from the acclaimed author of The Unbroken Thread. Over the past two generations, U.S. leaders deregulated big business on the faith that it would yield a better economy and a freer society. But the opposite happened. Americans lost stable, well-paying jobs, Wall Street dominated industry to the detriment of the middle class and local communities, and corporations began to subject us to total surveillance, even dictating what we are, and aren't, allowed to think. The corporate titans and mega-donors who aligned themselves with this vision knew exactly what they were getting: perfect conditions for what Sohrab Ahmari calls private tyranny. Drawing on original reporting and a growing chorus of experts who are sounding the alarm, Ahmari chronicles how private tyranny has eroded America's productive economy and the liberties we take for granted-from employment agreements that gag whistleblowers, to Big Finance's takeover of local fire departments, to the rigging of corporate bankruptcy to deny justice to workers and consumers--illuminating how these and other developments have left millions feeling that our livelihoods are insecure. And he shows how ordinary Americans can fight back, by restoring the economic democracy that empowered and uplifted millions of working-class people in the twentieth century. Provocative, original, and cutting across partisan lines, Tyranny, Inc. is a revelatory read on the most important political story of our time"--